Edukasi Manfaat Jahe Bagi Pasien Anemia Dan Masyarakat - Yasinta Rakanita; Viani Anggi; Yenni Putri Lestari; Muh. Afif Wahyudi Eyato (Jurnal Insan Pengabdian Indonesia, 2023)
Anemia is a condition of deficiency of red blood cells which is the main cause due to iron deficiency. The ginger plant is well known by the public as a spice in the kitchen, but its benefits in helping to recover from anemia are not well understood by our society. The incidence of chronic iron deficiency anemia in pregnant women was found to have a relationship with the incidence of stunting in children. The purpose of community service activities to increase the knowledge, skills and attitudes of the community about plants that are efficacious in anemia is very appropriate to do in Maku Village. The implementation method chosen was in the form of four parallel activities, namely education, health checks, distribution of basic necessities, and making TOGA (as a form of sustainability of this activity). The results obtained for knowledge increased by 50%, and skills 30%, and attitudes 50%. Overall the community gave a very good satisfaction response to this activity.